Czech And Slovak Cultural Dimensions And Advertising - Svetlík, Jaroslav (Communication Today, 2025)
The article covers the attitude to advertising as the most dominant tool of marketing communication. Advertising National culture is one of the frequent topics of professional discussions on advertising in the sphere of inter-national advertising, most of all in terms of standardization, adaptation and localization of advertising. Probably the best known model which describes the divergences of national cultures is the model of cultural dimensions of the Dutch academic Geert Hofstede. In the ﬁrst part of this paper the author describes four out of ﬁve cultural dimensions including their application in the ﬁeld of marketing communication. Subsequently the results of large surveys through VSM 94 questionnaire in the Czech (Světlík) and Slovak republic (Gecíková) are presented and the ﬁnal data are compared with selected EU countries and the USA. On the basis of Kogut’s methodology and established data the cultural distance of both countries was calculated and compared with other countries of the EU. The results show that people from the Czech Republic and the Slovak Republic are in comparison with other EU countries very close to each other from the point of cultural distance. In the third part of the paper there are possible recommendations for the cluster of these two countries presented particularly in advertising appeals, forms and execution of advertising. The author pointed out that the product category and features of the target group have a very strong inﬂuence on selection of advertising strategy components.